PENDIDIKAN DAN MUTU MANUSIA - Prima Roza (Fakultas Seni Rupa dan Desain ITB, 2007)
Education is taken to be the deliberate organized attempt to help people to become intelligent (Robert M. Hutchinson, 1998). Education leads people along the way to an understanding. Education is the only way to take human-being towards more productive, and more useful life. This article is trying to overview the role of education in producing quality people, so that they will be able to become pioneers for the great future of the nation.